On Metaphoric Features in Contemporary Russian Television Commentary - Борисовна Лихачева, Алла (Slavistica Vilnensis, 2000)
The investigation was carried out on the basis of Russian television news and comment broadcasts dating from the period from the beginning of 1997 to the end of April 2000). It revealed how much the language of television commentaries has changed in comparison with the years of perestroika. The analysis confirms the social nature of metaphors in the Russian mass media, and the interplay of life and language. It also shows some new phenomena in the language of Russian television broadcasts: stylistic polyphony, a partiality for colloquial aesthetics, and the expansion of informal and popular expressions.